Order–disorder transition in the two-dimensional interacting monomer-dimer model: Ising criticality. (9th October 2015) - Park, Su-Chan
Abstract: We study the order–disorder transition of the two-dimensional interacting monomer-dimer model (IMD) which has two symmetric absorbing states. To be self-contained, we first estimate numerically the dynamic exponent z of the two-dimensional Ising model. From the relaxation dynamics of the magnetization at the critical point, we obtain, or, where and are exactly known exponents. We then compare the critical relaxation of the order parameter at the transition point of the IMD with that of the Ising model. We find that the critical relaxation exponent is in good agreement with the Ising model, unlike the recent claim by Nam et al (2014 J. Stat. Mech . P08011). We also claim that the Binder cumulant is not an efficient quantity to locate the order–disorder transition point of the model with two symmetric absorbing states.